2011
DOI: 10.1111/j.1365-3156.2011.02792.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to first‐line tuberculosis drugs in three cities of Nigeria

Abstract: Summaryobjectives To determine the levels of resistance to first-line tuberculosis drugs in three cities in three geopolitical zones in Nigeria.methods A total of 527 smear-positive sputum samples from Abuja, Ibadan and Nnewi were cultured on BACTEC-MGIT 960. Drug susceptibility tests (DST) for streptomycin, isoniazid, rifampicin and ethambutol were performed on 428 culture-positive samples on BACTEC-MGIT960.results Eight per cent of the specimens cultured were multi-drug-resistant Mycobacterium tuberculosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 11 publications
7
34
1
Order By: Relevance
“…Previous studies in Ethiopia reported that the proportion of resistance to isoniazid was within a range of 1.9%–21.4% [3, 11]. Our finding is similar to a rate of resistance 10.0% and 9.9% reported in other African countries such as Nigeria, Abuja [27], and Tanzania [28], respectively while studies in Central African Republic [29], Somalia [30], and Zambia [31] reported a lower resistance rate of 5.8%, 5.7%, and 4.5%, respectively. The relatively high proportion of isoniazid resistance in this study might be due to the common use of the drug in the national TB control programme for longer time because of its accessibility.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies in Ethiopia reported that the proportion of resistance to isoniazid was within a range of 1.9%–21.4% [3, 11]. Our finding is similar to a rate of resistance 10.0% and 9.9% reported in other African countries such as Nigeria, Abuja [27], and Tanzania [28], respectively while studies in Central African Republic [29], Somalia [30], and Zambia [31] reported a lower resistance rate of 5.8%, 5.7%, and 4.5%, respectively. The relatively high proportion of isoniazid resistance in this study might be due to the common use of the drug in the national TB control programme for longer time because of its accessibility.…”
Section: Discussionsupporting
confidence: 88%
“…These are cities situated in three different geopolitical zones of Nigeria, as reported in Lawson et al , 2011 [2]. Five hundred twenty patients were recruited (520), including 433 newly diagnosed patients with pulmonary TB (PTB) and 87 patients with PTB who had failed to respond to first-line TB treatment attending TB diagnostic centres in three different geopolitical zones of Nigeria.…”
Section: Methodsmentioning
confidence: 99%
“…(2011) in Nigeria using molecular markers and we estimate the recent TB transmission rate in Nigeria [2]. We also identify the main clades of circulating genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…9 MDR-TB is recognized as an emerging problem in Nigeria in which 8% of diagnosed cases were MDR-TB, and it is strongly associated with previous treatment. 10 Kazakhstan is one of 14 nations having high morbidity to MDR-TB with resistance to isoniazid and rifampicin. 11 In 2006 the World Health Organization estimated that nearly 500,000 cases of MDR-TB occurred with new cases of XDR-TB (a MDR-TB instance that is also resistant to a fluoroquinolone and at least one second line agent) reported in 45 nations on all five continents.…”
Section: Introductionmentioning
confidence: 99%